Deletion of junctional adhesion molecule A from platelets increases early‐stage neointima formation after wire injury in hyperlipidemic mice. Issue 8 (17th February 2017) - Zhao, Zhen; Vajen, Tanja; Karshovska, Ela; Dickhout, Annemiek; Schmitt, Martin M.; Megens, Remco T.A.; von Hundelshausen, Philipp; Koeppel, Thomas A.; Hackeng, Tilman M.; Weber, Christian; Koenen, Rory R.
Abstract: Platelets play an important role in the pathogenesis of vascular remodelling after injury. Junctional adhesion molecule A (JAM‐A) was recently described to regulate platelet activation. Specific deletion of JAM‐A from platelets resulted in increased reactivity and in accelerated progression of atherosclerosis. The aim of this study was to investigate the specific contribution of platelet‐derived JAM‐A to neointima formation after vascular injury. Mice with or without platelet‐specific (tr)JAM‐A‐deficiency in an apolipoprotein e (apoe −/− ) background underwent wire‐induced injury of the common carotid artery. Ex vivo imaging by two‐photon microscopy revealed increased platelet coverage at the site of injury in trJAM‐A‐deficient mice. Cell recruitment assays showed increased adhesion of monocytic cells to activated JAM‐A‐deficient platelets than to control platelets. Inhibition of αM β2 or GPIbα, but not of CD62P, suppressed those differences. Up to 4 weeks after wire injury, intimal neoplasia and neointimal cellular content were analysed. Neointimal lesion area was increased in trJAM‐A −/− apoe −/− mice and the lesions showed an increased macrophage accumulation and proliferating smooth muscle cells compared with trJAM‐A +/+ apoe −/− littermates 2 weeks, but not 4 weeks after injury. Re‐endothelialization was decreased in trJAM‐A −/− apoe −/− mice compared with controls 2 weeks after injury, yet it was complete in both groups after 4 weeks. A platelet gain of function by deletion of JAM‐A accelerates neointima formation only during earlier phases after vascular injury, through an increased recruitment of mononuclear cells. Thus, the contribution of platelets might become less important when neointima formation progresses to later stages.